Analysis of ancient and modern horse genomes reveals the critical impact of lncRNA-mediated epigenetic regulation on horse domestication - Xu, Baoyan; Yang, Guixian; Jiao, Baowei; Zhu, Hao (Frontiers in Genetics, 2022)
Background The domestication of horses has played critical roles in human civilizations. The excavation of ancient horse DNA provides crucial data for studying horse domestication. Studies of horse domestication can shed light on the general mechanisms of animal domestication. Objective We wish to explore the gene transcription regulation by long noncoding RNAs (lncRNAs) that influence horse domestication. Methods First, we assembled the ancient DNA sequences of multiple horses at different times and the genomes of horses, donkeys, and Przewalski horses. Second, we extracted sequences of lncRNA genes shared in ancient horses and sequences of lncRNA genes and the promoter regions of domestication-critical genes shared in modern horses, modern donkeys, and Przewalski horses to form two sample groups. Third, we used the LongTarget program to predict potential regulatory interactions between these lncRNAs and these domestication-critical genes and analyzed the differences between the regulation in ancient/modern horses and between horses/donkeys/Przewalski horses. Fourth, we performed functional enrichment analyses of genes that exhibit differences in epigenetic regulation. Results First, genes associated with neural crest development and domestication syndrome are important targets of lncRNAs. Second, compared with undomesticated Przewalski horses, more lncRNAs participate in the epigenetic regulation in modern horses and donkeys, suggesting that domestication is linked to more epigenetic regulatory changes. Third, lncRNAs’ potential target genes in modern horses are mainly involved in two functional areas: (a) the nervous system, behavior, and cognition, and (b) muscle, body size, cardiac function, and metabolism. Conclusion Domestication is linked to substantial epigenetic regulatory changes. Genes associated with neural crest development and domestication syndrome underwent noticeable lncRNA-mediated epigenetic regulation changes during horse domestication.